Rancang Bangun Media Pembelajaran Interaktif Materi Operasi Hitung Untuk Sekolah Dasar Berbasis Android - Rahayu, Raden Erwin Gunadhi; Julianto, Indri Tri; Nurul Muttaqin, Epwan (Institut Teknologi Garut, 2025)
This research aims to design and develop android-based interactive learning media to help grade 1 elementary school students understand addition and subtraction operations. Multimedia Development Life Cycle (MDLC) includes the stages of concept, design, material collecting, assembly, testing, and distribution. The learning media is built using Adobe Animate and equipped with gamification elements such as badges, countdown, and score to increase student engagement. Alpha and beta testing were conducted on users, with beta testing results showing a user satisfaction score of 87.4% based on a Likert scale. The results show that the developed interactive application is feasible to be used as an alternative to learning mathematics in elementary schools.